Criterion for convexity of a domain of a Euclidean space - Vyhovs'ka, I. Yu.; Zelinskii, Yu. B. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We establish an external criterion for the convexity of a domain of a Euclidean space.